110 DO CYCLE 1 AND 6 PEDIATRIC CLERKSHIP STUDENTS HAVE THE SAME WEB SITE NEEDS?. (1st January 2006) - McBurney, P. G.; Bowman, C. M.; Blue, A. V.; Mauldin, M.; Darden, P. M.
Abstract : Purpose: To examine pediatric clerkship students' perspectives on a clerkship Web site designed to provide structure and increase interactions and to determine if cycle 1 (inexperienced) students' needs are different from cycle 6 (experienced) students' needs. Methods: Web site created through the course management system, WebCT, for clerkship in 2004. Components included student schedules, resident schedule links, helpful Web site links, clerkship syllabus, small group cases/questions, and any lecture/case discussion materials provided by faculty. Two focus groups were held by nonpediatric faculty/staff not involved directly in clerkship. Participation was voluntary and the focus groups were held at the end of the 8-week clerkships for cycles 1 and 6. Focus group questions were based on Chickering and Gamson's principles. 1 Results: Eleven students participated in each focus group (n = 22). Prominent themes were as follows: (a) Students liked the logistical information available and felt this central access better prepared them. (b) Students felt the Web site was a positive learning experience; however, they did not feel that the Web site increased learning interactions between students or between students and faculty. (c) There were no substantive differences in the themes from cycle 1 and cycle 6. Conclusions: There appears to be no need to create specific Web site features for students with different levels of experience (eg, cycle 1 versus cycle 6). A Web site is valuable to clerkship students. However, having a Web site available for clerkship materials does not necessarily increase interaction between learners or learners and faculty.